2023
DOI: 10.1088/1674-4527/ace51f
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-explosion Effervescent Zone for the Circumstellar Material in SN 2023ixf

Abstract: I present the effervescent zone model to account for the compact dense circumstellar material (CSM) around the progenitor of the core collapse supernova (CCSN) SN~2023ixf. The effervescent zone is composed of bound dense clumps that are lifted by stellar pulsation and envelope convection to distances of $\approx {\rm tens} \times \AU$, and then fall back. The dense clumps provide most of the compact CSM mass and exist alongside the regular (escaping) wind. I crudely estimate that for a compact CSM within $R_{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The spectropolarimetric observations presented in this work align with the conclusions of Smith et al (2023), where the CSM was also suggested as being asymmetric from the lack of blueshifted absorption components in the narrow P Cygni profiles. Another possible model for the CSM includes the presence of a preexplosion effervescence zone (see Soker 2023). The polarimetry results suggest that such an effervescence zone may be flat due to the rotation of the progenitor or binary interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The spectropolarimetric observations presented in this work align with the conclusions of Smith et al (2023), where the CSM was also suggested as being asymmetric from the lack of blueshifted absorption components in the narrow P Cygni profiles. Another possible model for the CSM includes the presence of a preexplosion effervescence zone (see Soker 2023). The polarimetry results suggest that such an effervescence zone may be flat due to the rotation of the progenitor or binary interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the progenitor experienced a relatively enhanced mass loss (M M 2 10 4   » ´yr −1 ) until several years before the explosion and experienced an extreme mass loss (M M 10 10 3 0 -  =yr −1 ) later during 1-3 yr before the explosion. It is also worth mentioning that the discrepancy of mass-loss rate maybe originates from nonhomogeneous CSM (Beasor et al 2023;Smith et al 2023;Soker 2023).…”
Section: Mass-loss Ratementioning
confidence: 99%
“…In such a binary scenario, eruptive mass loss from a single RSG may not be the driving force behind the dense CSM that we observe. In addition, Soker (2021Soker ( , 2023 suggested that the long-lived effervescent zone formed around RSGs could be an alternative scenario for the dense CSM around the progenitors of Type II SNe.…”
Section: Comparison With Other Precursor Studiesmentioning
confidence: 99%